A 2007 Social Accounting Matrix (SAM) for Swaziland - van Seventer, Dirk (International Food Policy Research Institute, 2014)
A 2007 Social Accounting Matrix (SAM) for Swaziland is constructed using data that available during the second half of 2011. The SAM is update of the 2004 SAM using UN National Accounts data, UNComTrade data and selected publications from the IMF, WorldBank and OECD/ADB. The SAM provides a detailed representation of the Swaziland economy. It separates 22 activities and 24 commodities; labor is disaggregated by 3 skill groups; and households into 6 groups based on the rural/urban and income status of the household head. The SAM is a useful database for conducting economy-wide impact assessments, including SAM-based multiplier analysis and computable general equilibrium (CGE) modeling.